Removal of triclosan from aqueous solution via adsorption by kenaf‐derived biochar: Its adsorption mechanism study via spectroscopic and experimental approaches - Cho, Eun Ji; Kang, Jin Kyu; Moon, Joon Kwan; Um, Byung Hwan; Lee, Chang Gu; Jeong, Sanghyun; Park, Seong Jik (Journal of Environmental Chemical Engineering, 2021)
Biochars derived from kenaf were synthesized to adsorb triclosan from an aqueous solution. The triclosan adsorption mechanism of the biochars pyrolyzed at various temperatures (300, 400, 600, and 750 °C) was explored using physical/chemical analyses (FE-SEM, EDS, EA, XRF, pHpzc, N2 adsorption-desorption, SAXS, ATR-FTIR, and XPS). The triclosan adsorption by the kenaf biochar increased as the pyrolysis temperature increased, except for 450 °C, which showed the lowest adsorption capacity. The kenaf biochar synthesized at 750 °C (KNF-750) exhibited the highest adsorption capacity owing to its high aromatic moiety and large specific surface area. Kinetic adsorption by KNF-750 was well fitted with the pseudo-second-order model, with equilibrium attained within 3 h. The maximum triclosan adsorption capacity of KNF-750 obtained from the Langmuir model with a high correlation coefficient was 77.4 mg/g. Triclosan adsorption sharply decreased at an initial solution pH of 5 because a final solution pH higher than 9 caused dissociation of triclosan. A 90% removal of triclosan was achieved with 4 g/L of KNF-750. The adsorption of triclosan was endothermic, with an enthalpy change of 32.8 kJ/mol. XPS analysis proved that triclosan was adsorbed on the surface of biochar by the disappearance of inorganic Cl and the appearance of organic Cl.
Keywords: Adsorption capacities; Adsorption mechanism; Biochar; Experimental approaches; Mechanism studies; Physical-chemical analysis; Pyrolysis temperature; Solution pH; Synthesised; Triclosan; Adsorption mechanism; Biochar; Kenaf; Pyrolysis temperature; Triclosan